2008
DOI: 10.1136/bjsm.2008.049270
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between knee joint laxity and knee joint mechanics during the menstrual cycle

Abstract: Knee laxity correlates positively with knee joint loads, and increased knee laxity during the menstrual cycle may be a potential risk factor for anterior cruciate ligament injuries in certain women during sports activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
84
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(93 citation statements)
references
References 44 publications
(50 reference statements)
0
84
1
4
Order By: Relevance
“…Although the overall postural changes were underestimated in the literature, knee and lower extremity alignment (51), knee joint position sense (25), knee joint laxity and loading (12), gait parameters (52), postural control, kinesthesia, and balance (13,14) have all been relevant since the menstrual cycle might be a potential risk factor for anterior cruciate ligament injuries in active women. Postural stability parameters were assessed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the overall postural changes were underestimated in the literature, knee and lower extremity alignment (51), knee joint position sense (25), knee joint laxity and loading (12), gait parameters (52), postural control, kinesthesia, and balance (13,14) have all been relevant since the menstrual cycle might be a potential risk factor for anterior cruciate ligament injuries in active women. Postural stability parameters were assessed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, increased levels of progesterone in the luteal phase were related to increased intensity of premenstrual complaints (anxiety, tension, irritability) (6,7), while in other studies decreased progesterone levels were found to be related to more pronounced negative mood changes (8,9). Moreover, the neuromusculoskeletal effects relating to muscle strength and stretch reflex (10), ligament laxity (11), biomechanical characteristics (12), and postural control (13,14) throughout the menstrual cycle have been investigated in the literature in order to determine the relationship between injury mechanisms in women and the differences between the sexes. Menarche itself was declared to be a risk factor in some sports and conditions (15).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of women incur knee injuries during sports activities (Beynnon et al 2005;Eiling et al 2007;Kjaer and Hansen 2008;Hansen et al 2009b; Lee et al 2013aLee et al , 2015. The incidence, especially of non-contact anterior cruciate ligament injuries, is 2 to 8 times greater in women compared to men when participating in the same sports activities (Park et al 2009a, b;Hansen et al 2009b;Boden et al 2010;Lee et al 2013a;Stijak et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…6. Although cyclic variations in anterior knee laxity may be sufficient to alter knee joint neuromechanics, 111,112 we do not yet fully understand the clinical implications of cyclic changes in knee laxity on weight-bearing knee-joint function. 7.…”
Section: Because Of the Individual Variabilities In Hormonementioning
confidence: 99%